1966
DOI: 10.1017/s0003356100034541
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin N of sheep. Age, breed and seasonal distribution

Abstract: The occurrence of Hb N in sheep has been investigated by means of starch gel electrophoresis.In lambs, Hb N occurred in higher relative amounts than in adults, but not until 9 days of age. One-month-old lambs often showed an Hb N content as high as 10–30%.Haemoglobin N was observed most in sheep of phenotype AA, less in those of type AB and was found to be absent in BB animals. It was also provoked experimentally by bleedings in sheep of types AA and AB but not in those of type BB.Comparisons between breeds sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…After starch gel electrophoresis, this variant could be observed as an additional band, the C band, which was not present in the animals before the onset of the disease. This new band, appearing identical to that described by Efremov and Braend (1966), Huisman and Kitchens (1968), Tucker (1966) and Kitchen et al (1968), was reported for the first time as being associated with specific disease syndromes or with the recovery from these diseases.…”
supporting
confidence: 83%
“…After starch gel electrophoresis, this variant could be observed as an additional band, the C band, which was not present in the animals before the onset of the disease. This new band, appearing identical to that described by Efremov and Braend (1966), Huisman and Kitchens (1968), Tucker (1966) and Kitchen et al (1968), was reported for the first time as being associated with specific disease syndromes or with the recovery from these diseases.…”
supporting
confidence: 83%
“…Efremov (1978) derived an empirical PA relation by adopting Cepheids in Galactic, in M31, and in LMC clusters, whose age was estimated independently. Magnier et al (1997) derived a new semi-empirical PA relation and used Cepheids in NGC 206, the super association in M31, to trace the age distribution and, in turn, the SFH in this region, located at the intersection of two spiral arms.…”
Section: Age Of the Cepheidsmentioning
confidence: 99%
“…High altitude conditions, actual or simulated, can also cause increased synthesis of HbC (Boyer et al 19683;Blunt, Perry & Lane, 1970). In addition, HbC can regularly be found in young lambs with Hb type A or AB when erythropoiesis is very active during rapid growth (van Vliet & Huisman, 1964;Efremov & Braend, 1966;Tucker, 1966).…”
Section: (6) Frequencies In Diyerent Breedsmentioning
confidence: 99%